Effect of Play Approach Against Learning Outcomes in Soccer Games - Rinaldi Aditya; Filli Azandi; M, Benny Aprial (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2020)
In general, the purpose of this action research study is to improve learning outcomes of dribbling in a football game through a play approach to physical education. In addition, this study was conducted to obtain information about the application of the play approach for grade VI elementary school students and find out the effectiveness, efficiency and improvement of learning outcomes of dribbling in football games for physical education for 6th grade elementary school students. This action research research uses a qualitative approach. The subjects in this study were grade VI students of SD Negeri Janji, North Sumatra. To test the effectiveness of playing approach patterns can be seen from psychomotor data and results of dribbling tests in football games. In the results of the previous learning test (pre-test) obtained 30% of the expected criteria. While the level of effectiveness in the pre-test through the play approach was obtained 70% of the suggested criteria. Then proceed through the pattern of playing approaches in the game of football, the level of effectiveness in the post test obtained 86% of the expected criteria, meaning an increase of 66%. Based on the results of this study it can be concluded that: (1) with a play approach to physical education, students can learn more effectively and efficiently, and improve learning outcomes dribbling. (2) with a play approach pattern, students are more motivated and active in following the learning process.